Pengembangan E-Modul Interaktif dengan PBI untuk Meningkatkan Kemampuan Pemecahan Masalah Aljabar Siswa Kelas VII - Kurniawan, Okta; Sukestiyarno, YL; Hidayah, Isti (Universitas Muria Kudus, 2023)
This study aims to (1) analyze students' problem-solving skills before using the results of developing interactive e-modules in PBI learning, (2) produce interactive e-modules in PBI learning that can be used as materials or tools for teachers to facilitate learning activities, (3) produce interactive e-modules in PBI learning with quality, namely interactive e-modules for PBI learning that meet valid, practical and effective criteria so that they can help students improve their problem-solving skills. The research method used an R D approach. The subject of this research was taken based on a purposive sampling technique. While the validators consisted of lecturers from the Semarang State University Postgraduate Program and 2 (two) teachers from SMP 16 Bengkulu city. Data collection was carried out through tests, observations, questionnaires, and documentation. Data analysis was performed using descriptive and inferential statistics using the Wilcoxon test. The results of this study concluded that (1) The students' problem-solving skills prior to learning using interactive e-module development in mathematics learning showed both groups in the medium category, (2) The results of interactive e-module development in Mathematics learning on Class VII Algebra story material met valid and practical criteria, (3) The results of interactive e-module development in Mathematics learning in Class VII Algebra word problems were considered effective because it had been proven from differences in the problem solving abilities of students in the control group and the treatment after treatment.